The Effect of Franchise No-Poaching Restrictions on Worker Earnings - Callaci, Brian; Gibson, Matthew; Pinto, Sérgio; Steinbaum, Marshall; Walsh, Matt (The Review of Economics and Statistics, 2024)
Abstract We evaluate the nationwide impact of the Washington State Attorney General's 2018-20 enforcement campaign against no-poach clauses in franchising contracts, which prohibited worker movement across locations within a chain. Implementing a staggered difference-in-differences research design using Burning Glass Technologies job vacancies and Glassdoor salary reports from numerous industries, we estimate a 6% increase in posted annual earnings from the job vacancy data and a 4% increase in worker-reported earnings.